“O código daria remédio a tudo isso”: impasses na introdução do registro civil no Brasil (1874-1916) - Santos, Ana Gabriela Da Silva [UNIFESP] (2018)
In this work a mapping of the debates about the functioning of the civil registry in Brazil was carried out, as well as the impasses found for its implementation, since its enactment as a decree (1874), ending in the year in which the Civil Code of 1916 was approved, which the referendum. It sought to highlight its legislative aspects, drawing attention to some implications for the production of population statistics and their repercussion in the field of law. In the name of the need for a modern legal system in the nineteenth century, civil registration was increasingly conceived as a key instrument for the organization and maintenance of society in the eyes of those who spoke in the name of consolidating a state apparatus. However, this paper intends to show how complex this process was in view not only of the relationship between the State and the Catholic Church, but also of the ways of regulating the "private" space of families (the "home" government) and the difficulties the agents of these institutions in the face of the dispersion and heterogeneity of the population.